Studi in Silico Senyawa Flavonoid sebagai Inhibitor Angiotensin-Converting Enzyme (ACE) pada Hipertensi - Ahmad Hakiki; Miftahul Jannah; Jantje W. Souhaly (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
Hypertension is a disease that is the main cause of increased risk of cardiovascular disease. One of the targets of hypertension therapy is Angiotensin-Converting Enzyme (ACE), which plays a role in the formation of angiotensin II. This study aims to analyze the potential of flavonoid and phenolic compounds as ACE inhibitor candidates using an in silico approach. The compounds analyzed included quercetin, kaempferol, catechin, gallic acid, and chlorogenic acid, with captopril as a positive control. The study was conducted through compound identification, drug-likeness screening using SwissADME, toxicity prediction using ProTox-II, molecular docking using PyRx, and molecular interaction analysis using BIOVIA Discovery Studio. The results showed that all compounds met the drug-likeness criteria with a maximum of one violation of Lipinski's rule and had a relatively low level of toxicity. Molecular docking results showed that quercetin had the best binding affinity value of -9.2 kcal/mol, followed by chlorogenic acid (-9.0 kcal/mol) and kaempferol (-8.5 kcal/mol). Molecular interaction analysis showed that all three compounds are capable of forming hydrogen bonds and hydrophobic interactions with residues in the active site of ACE. Based on these results, quercetin has the potential to be a promising ACE inhibitor candidate as a natural-based antihypertensive agent.